An Equal Right to Inherit? Women's Land Rights, Customary Law and Constitutional Reform in Tanzania. (June 2017) - Dancer, Helen
This article explores contemporary contestations surrounding women's inheritance of land in Africa. Legal activism has gained momentum, both in agendas for law reform and in test case litigation, which reached the United Nations Committee on the Elimination of Discrimination against Women in ES and SC v. United Republic of Tanzania. Comparing the approach of Tanzania to that of its neighbours, Uganda, Kenya and Rwanda, this article explores patterns of resistance and omission towards enshrining an equal right to inherit in land and succession laws. It identifies two main reasons: neoliberal drivers for land law reform of the 1990s and sociopolitical sensitivity surrounding inheritance of land. It argues that a progressive approach to constitutional and law reform on women's land rights requires understanding of the realities of claims to family land based on kinship relations. It calls for a holistic approach to land, marriage and inheritance law reform underpinned with constitutional rights to equality and progressive interpretations of living customary law.